2015
DOI: 10.15578/bawal.7.3.2015.155-163
|View full text |Cite
|
Sign up to set email alerts
|

Struktur Tingkat Trofik Komunitas Ikan Di Waduk Wadaslintang Kabupaten Wonosobo, Jawa Tengah

Abstract: ABSTRAKWaduk Wadaslintang memiliki potensi perikanan yang cukup besar baik perikanan tangkap maupun perikanan budidaya. Kegiatan penangkapan ikan di waduk Wadaslintang saat ini sudah cukup tinggi, yang akan berdampak langsung pada struktur komunitas ikan yang menyebabkan pergeseran pola hubungan antara pemangsa, mangsa atau pesaing pada berbagai tingkat trofik. Tujuan penelitian ini untuk mengetahui pola hubungan antar kelompok ikan berdasarkan tingkat trofik dari tingkat trofik terendah sampai kepada ikan kar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The trophic level estimated of bullet tuna in Prigi Coast is 3.7, positioning it as a carnivore that opportunistically eats various food types and preferred ate fish and cructacean. Fatah and Adjie (2015) state that fish catching is capable of altering the spatial distribution and fish abundance, which will affect species interaction and trophic structure in general. The trophic level of a particular fish can be affected by life expectancy (size), gonads, ecomorphology, behavior, intraspecies and interspecies competition, as well as distribution of resources and parasites (Elliot & Hemingway 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The trophic level estimated of bullet tuna in Prigi Coast is 3.7, positioning it as a carnivore that opportunistically eats various food types and preferred ate fish and cructacean. Fatah and Adjie (2015) state that fish catching is capable of altering the spatial distribution and fish abundance, which will affect species interaction and trophic structure in general. The trophic level of a particular fish can be affected by life expectancy (size), gonads, ecomorphology, behavior, intraspecies and interspecies competition, as well as distribution of resources and parasites (Elliot & Hemingway 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It was showed in this study, the high GSI were found in treatment B and C with the stage III, IV and V. In this study, the GSI value obtained was less than 20%. Therefore, its indicated that P. tawarensis are included in the group of fish with low GSI values and can be categorized as fish that can spawn more than once per year, according to Fatah et al [22], the GSI value ≤ 20% is a group of fish that can spawn more than once a year. The use of Oodev hormone on treatment B and C was able to ripen brood fish of P. tawarensis.…”
Section: Discussionmentioning
confidence: 99%